Modification of the existing maximum residue levels and setting of import tolerances for fluopyram in various crops - EFSA (European Food Safety Authority); Giulia Bellisai; Giovanni Bernasconi; Alba Brancato; Luis Carrasco Cabrera; Irene Castellan; Monica Del Aguila; Lucien Ferreira; German Giner Santonja; Luna Greco; Samira Jarrah; Renata Leuschner; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Bayer AG Crop Science Division submitted a request to the competent national authority in Italy to modify the existing maximum residue level (MRL) for the active substance fluopyram in kiwi. Additionally, the applicants Bayer Crop Science SA and Bayer SAS Crop Science Division submitted two applications to the competent national authority in Germany to modify the MRLs for fluopyram in certain stem vegetables, seed spices, apples and soyabeans based on intended EU uses as well as to lower the existing EU MRL in pome fruits and to raise the existing EU MRL in peanuts on the basis of authorised use of fluopyram in the USA. The data submitted in support of the request were found to be sufficient to derive MRL proposals for all the crops under assessment except for palm hearts and bamboo shoots. Adequate analytical methods for enforcement are available to control the residues of fluopyram in commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term intake of residues resulting from the use of fluopyram according to the reported agricultural practices is unlikely to present a risk to consumer health. A long‐term consumer intake concern is identified if the current MRL of 0.8 mg/kg in pome fruits is maintained and new MRLs for other commodities under consideration are supported, with apples being the highest contributing commodity to the diet for which exposure exceedances were noted. The chronic risk for consumers is unlikely if a lower MRL of 0.6 mg/kg in pome fruits proposed by the applicant is considered. Further risk manager considerations are required.